1987
DOI: 10.1073/pnas.84.5.1417
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of aspirin and salicylate in relation to inhibition of arachidonate cyclooxygenase and antiinflammatory activity.

Abstract: Among the nonsteroid antiinflammatory drugs there is generally a close correlation between the potency of their inhibition of arachidonate cyclooxygenase, and thus prostaglandin production, and their antiinflammatory activity.One anomaly in this generalization is that whereas aspirin and salicylate are equipotent as antiinflammatory agents, salicylate is less active than aspirin in inhibiting prostaglandin production in vitro. Using rats, we have now measured the concentrations of aspirin and salicylate in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
0
3

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(121 citation statements)
references
References 19 publications
9
109
0
3
Order By: Relevance
“…Here we show that aspirin is =100 times more potent than salicylate as an inhibitor of COX-1 in intact cells but only twice as potent as an inhibitor of COX-2. These observations may explain those of Higgs et al (30) showing that salicylate and aspirin were approximately equipotent inhibitors of COX activity in explants of acutely inflamed tissue (COX-2?). However, aspirin was found to be considerably more potent than salicylate as an inhibitor of PGs in the serum (COX-1?).…”
Section: Discussionsupporting
confidence: 67%
“…Here we show that aspirin is =100 times more potent than salicylate as an inhibitor of COX-1 in intact cells but only twice as potent as an inhibitor of COX-2. These observations may explain those of Higgs et al (30) showing that salicylate and aspirin were approximately equipotent inhibitors of COX activity in explants of acutely inflamed tissue (COX-2?). However, aspirin was found to be considerably more potent than salicylate as an inhibitor of PGs in the serum (COX-1?).…”
Section: Discussionsupporting
confidence: 67%
“…Subsequently, we used aspirin at the final concentration of 20 μM because it inhibited PGE 2 synthesis by ~80% in our experimental conditions. As aspirin can be deacetylated in these cells to form salicylic acid [22], we performed the same experiment with equivalent concentrations of salicylic acid and demonstrated that the inhibition observed with aspirin was not due to its deacetylated product. A range of concentrations of 12-HPETE was added to IL-1β activated A549 cells that immediately were exposed to 20 μM aspirin.…”
Section: Prevention By Hydroperoxides Of the Inhibition Of Pghs-2 By mentioning
confidence: 99%
“…After administration, aspirin undergoes rapid hydrolysis to generate salicylic acid (SA), and it is this phenolic acid that may be responsible for the persistence of the anti-in£ammatory e¡ect of aspirin. 2 Paterson et al, 3 using high-performance liquid chromatography (HPLC), gas chromatography^mass spectrometry (GCMS) and salicylate hydroxylase, demonstrated that SA and two of its hydroxylated metabolites were present in the serum of people who had not taken salicylate drugs, and they suggested that these phenolic acids may have had a dietary origin. Swain et al 4 determined SA in foodstu¡s using HPLC with UV detection and estimated that the dietary intake of SA was in the range 70^1100 mol per person per 24 h. Janssen et al 5 examined acid-treated urine using HPLC with £uorescence detection, and suggested that the dietary intake of SA was about 10 mol per person per 24 h. However, neither Swain et al nor Janssen et al had characterized the compound(s) they had determined.…”
Section: Introductionmentioning
confidence: 99%